Pandangan Masyarakat di Desa Tuntungan terhadap Mahasiswi Bercadar UINSU Medan - Vinky Raisyah; Suriyani Siregar; Nuraini Nuraini; Nabilah Aprilia; Poppy Indah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to discuss the views of the community in Tuntungan Village, Pancur Batu Sub-District, towards veiled students from the State Islamic University of North Sumatra Medan. Veiled students often face various responses from the community, ranging from acceptance to rejection. Some people think that the veil is part of a symbol of obedience in religion and the identity of Muslim women who obey the teachings of Islam. But others reject the use of the veil, because it is often influenced by negative stigmas that associate it with radicalism or terrorism. This research uses a qualitative method with a phenomenological approach to deeply understand the views of the community and the factors that influence it. This research found that there are differences in people's views that are not only nfluenced by religious understanding, but also by the level of education, exposure to information and direct interaction by veil users.